Upconversion Visible Light Emission in Yb/Pr Co-Doped Yttria-Stabilized Zirconia (YSZ) Single Crystals - Daini Wang (MDPI AG, 2021)
As a development on previous research on single crystals of Pr3+-doped yttria-stabilized zirconia (YSZ), we report here the preparation and optical properties of Yb/Pr co-doped YSZ single crystals with different Yb2O3 concentrations. Results from X-ray diffraction (XRD) and Raman spectroscopy indicated that all of the crystal samples had a cubic phase structure, and transmission was ≥88% in the 550–780 nm range. Photoluminescence (PL) under excitation with a 980 nm laser showed upconversion emission, and several peaks were observed centered on 448 nm, 508 nm, 525 nm, 542 nm, 617 nm and 656 nm. The effects of excited state absorption (ESA), energy transfer upconversion (ETU), cross relaxation (CR), and cooperative energy transfer (CET) on the upconversion luminescence and energy transition mechanism in YSZ crystals were further studied. The fluorescence lifetime of the 3P0 → 3H5 transition at 542 nm reached 207 μs, which shows that the samples are of potential use for laser and fluorescence output.